AN ANALYSIS OF EXPRESSIVE SPEECH ACTS IN ONLINE DISCUSSION THROUGH WHATSAPP GROUP - M, Asia; Asdar, Asdar; Lutfin, Nursamsilis (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
This study aimed to investigate an analysis of students’ expressive speech acts in online discussion through Whatssapp group. The method used was descriptive qualitative research, and the data source contained expressive speech acts between teacher and students in online teaching and learning. The data came from online teaching and learning interactions between teachers and students for Indonesian language in class VIII at SMP Negeri 35 Makassar with total of 246 students consisted of nine classes and a total of 56 students as respondents. The results found that expressive speech acts can be found everywhere, including in learning Indonesia subject through apologizing, tempting, motivating, hoping, praising, gratitude, thanking, congratulation, criticizing forms and functions of teacher and students’ expressive speech acts. It can be concluded that many expressive speech acts are used in the interactions between teachers and students in online discussion. This research can contribute to the interaction between students and teacher regarding the expressive speech acts in online teaching and learning interactions through WhatssApp group discussion.